2012
DOI: 10.4236/ajac.2012.39083
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Residual Solvents in Annatto Extracts Using a Static Headspace Gas Chromatography Method

Abstract: An analytical method for the quantification of residual solvents in annatto extracts, natural food colorants, was established using a static headspace gas chromatography (HSGC) coupled with a flame ionization detector (FID). As a sample diluent in a headspace sampling, dimethylformamide (DMF) was selected owing to its high capacity for dissolving both bixin-based and norbixin-based annatto extracts. The quantification of residual solvents was performed using the external standard method. The linearity of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Oh et al (3) reported that the analyses of the residual hexane in 87 commercial vegetable oils using HS-GC/FID showed values of the order of trace-2.8 mg/kg. Ito et al (5) reported that the residual hexane in six commercial bixin products using HS-GC/FID was of the order of ND-0.7 ppm. In this study, hexane was measured at less than 5 mg/kg, which complies with the maximum residue limits regulated by the Food Additives Code (1).…”
Section: Methods Validation For Hexane Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Oh et al (3) reported that the analyses of the residual hexane in 87 commercial vegetable oils using HS-GC/FID showed values of the order of trace-2.8 mg/kg. Ito et al (5) reported that the residual hexane in six commercial bixin products using HS-GC/FID was of the order of ND-0.7 ppm. In this study, hexane was measured at less than 5 mg/kg, which complies with the maximum residue limits regulated by the Food Additives Code (1).…”
Section: Methods Validation For Hexane Analysismentioning
confidence: 99%
“…A number of studies have been performed previously on the analysis of hexane in food products. A method to analyze the residual hexane in vegetable oil (3), beeswax (4), annatto extracts (5), and drug substance (6) was developed using headspace gas chromatography (GC). A method to analyze the residual hexane in olive oil (7) was developed using headspace-solid phase microextraction (SPME).…”
Section: Introductionmentioning
confidence: 99%
“…Oh et al (2005) found that hexane residue varied from trace amounts to 2.8 mg/kg in 87 commercial vegetable oils (9). Additionally, Ito et al (2012) evaluated 23 annatto extract products for hexane residue by applying HS-GC/FID, and nearly 91% of the samples were free of hexane and only two samples containing hexane in the value of 0.6 and 0.7 mg/kg (11). Ligor and Buszewski (2008) investigated the presence of some solvents including acetone, n-hexane, benzene, and toluene in various edible oils using SPME-GC-FID and SHS-GC-FID methods.…”
Section: Hexane Concentrationmentioning
confidence: 99%
“…The NIHS has researched and developed the analytical methodology in terms of specifications and standards for designated food additives (7)(8)(9)(10)(11)(12)(13)(14). …”
Section: Establishment Of Specifications and Standards For Food Additmentioning
confidence: 99%